2015
DOI: 10.1136/ejhpharm-2014-000608
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in the incidence of hospital-acquired MRSA following the introduction of a chlorine dioxide 275 ppm based disinfecting agent in a district general hospital

Abstract: BackgroundMethicillin-resistant Staphylococcus aureus (MRSA) and Clostridium difficile are major nosocomial pathogens whose control relies on effective antimicrobial stewardship and infection control practices. This study evaluates the impact of a chlorine dioxide-based disinfectant (275 ppm) on the incidence of hospital-acquired (HA) MRSA and HA-Clostridium difficile infection (CDI) in a district general hospital.MethodsThis study was carried out from November 2009 to September 2013. From November 2009 to Oct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Spore suspensions (U and P) from strains DS1748, R20291, and DS1813 at a concentration of 1 ϫ 10 6 spores per ml were exposed to 1,000 ppm NaDCC for 10 min in liquid form (recommended contact time), neutralized with sodium thiosulfate, and deposited onto sterile gowns. Spores were recovered as described previously (1,22). Second, spores were also spiked onto the gown surface, as described in the spore transfer section above, and spores were spiked onto the surfaces of hospital stainless steel and hospital vinyl flooring for each biological repeat and allowed to dry for 120 min in a category 2 biosafety laminar flow cabinet.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spore suspensions (U and P) from strains DS1748, R20291, and DS1813 at a concentration of 1 ϫ 10 6 spores per ml were exposed to 1,000 ppm NaDCC for 10 min in liquid form (recommended contact time), neutralized with sodium thiosulfate, and deposited onto sterile gowns. Spores were recovered as described previously (1,22). Second, spores were also spiked onto the gown surface, as described in the spore transfer section above, and spores were spiked onto the surfaces of hospital stainless steel and hospital vinyl flooring for each biological repeat and allowed to dry for 120 min in a category 2 biosafety laminar flow cabinet.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, when 275 ppm chlorine was applied to a clinical environment, there was a significant reduction in hospital-acquired infections from non-spore-forming bacteria (20,21). However, the inactivation of spores requires much higher concentrations, with the current recommendation for application of NaDCC in hospitals in England being 1,000 ppm available chlorine for 10 min to deactivate spores of C. difficile and Bacillus species (22,23). Although the working concentration of NaDCC has been shown to be effective in liquid culture (24), its application to working surfaces is less efficient for the inactivation of spores (25), and this reduced activity is exacerbated by the presence of organic substances, such as bodily fluids and feces, which have a neutralizing effect on the biocide (26).…”
mentioning
confidence: 99%
“…Another study, which was a low-quality controlled trial 173 compared two different types of antimicrobial curtain (impregnated with either silver, or QAC combined with polyorganosiloxane) to a standard curtain. There was a significant decrease in the number of curtains contaminated when comparing curtains impregnated with QAC and polyorganosiloxane (3/580, 0.5%) and a standard curtain (204/ There was inconsistent evidence of benefit reported by one RCT 161/162 , three controlled trials [175][176][177] and two ITS 178,179 studies investigating different types of cleaning and disinfection agents. One ITS, 178 which replaced hypochloric acid (concentration 1000ppm) with chlorine dioxide (concentration 275 ppm) reported a significant change in MRSA acquisition per 100 bed days/month at 12 months from the start of the intervention.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…There was a significant decrease in the number of curtains contaminated when comparing curtains impregnated with QAC and polyorganosiloxane (3/580, 0.5%) and a standard curtain (204/ There was inconsistent evidence of benefit reported by one RCT 161/162 , three controlled trials [175][176][177] and two ITS 178,179 studies investigating different types of cleaning and disinfection agents. One ITS, 178 which replaced hypochloric acid (concentration 1000ppm) with chlorine dioxide (concentration 275 ppm) reported a significant change in MRSA acquisition per 100 bed days/month at 12 months from the start of the intervention. Another ITS 179 reported that switching from cleaning with detergent wipes followed by alcohol wipes (details on ingredients and concentration not reported) to one wipe system (containing <0.5% benzalkonium chloride, <0.5% didecyl dimethyl ammonium chloride and <0.10% polyhexamethylene biguanide) in a general hospital setting, resulted in the reduction of the incidence of MRSA acquisition from 26.8 per 100,000pd to 9.4 per 100,000pd (p<0.0001).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Additional inactivation studies involving these two biocides and human coronaviruses do exist; however, those involving EtOH have typically only examined various hand sanitizer formulations ( Kratzel et al, 2020 ), while research involving NaOCl has been limited to coronaviruses existing prior to the emergence of SARS-CoV-2 ( Kampf et al, 2020 ; Janik et al, 2021 ). Furthermore, the direct effects of KMPS and ClO 2 on SARS-CoV-2 have yet to be reported in vitro , although both agents have displayed notable antimicrobial activity against a wide array of pathogens ( Su and D’Souza, 2012 ; Hinenoya et al, 2015 ; Morin et al, 2015 ; Conlon-Bingham et al, 2016 ; Praeger et al, 2018 ; Sonthipet et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%